Scientific contribution of the Brazilian CNPq Research Productivity fellows in dentistry - Valéria Gonzaga Botelho de Oliveira; Árlen Almeida Duarte de Sousa; Fabrício Emanuel Soares de Oliveira; Daniella Reis Barbosa Martelli; Eduardo Araújo; Ricardo Della Coletta; Hercílio Martelli Júnior (Brazilian Oral Research)
Abstract This study evaluated the scientific contribution of Brazilian CNPq Research Productivity fellows (PQ) in Dentistry by areas of activity. This cross-sectional study included 217 active PQ who were grouped into six groups: (1) Biomaterials, Prosthodontics, and Restorative Dentistry; (2) Public Health and Epidemiology; (3) Oral Pathology, Stomatology, and Dental Radiology; (4) Pediatric Dentistry and Child Health; (5) Dental Clinic (Periodontics, Endodontics, Orthodontics, Oral Surgery, and Implantology), and (6) Basic Areas (Histology, Biochemistry, Molecular Biology, Physiology, Microbiology, Immunology, and Pharmacology). The PQ were predominantly male (n = 122; 56.2%), received level 2 scholarships (n = 121; 55.8%), and performed research in the Southeast region of Brazil (n = 160; 73.73%). Regarding supervision of undergraduate, master's, and PhD students, both during their entire careers and in the last 5 years, the highest average was observed for PQs in the field of Public Health and Epidemiology, the only area with higher average supervision of master's than that of undergraduate and PhD students. PQ in Public Health and Epidemiology had the highest average number of papers published over their career and in the last 5 years, followed by PQ in Pediatric Dentistry and Child Health and Dental Clinic. The high productivity of PQ is demonstrated by modern research performance indicators. Their scientific publications are indexed in bibliometric databases such as WoS, Scopus, and SciELO. Addtionally, highlighted among the PQ was the time since initiation of their scientific careers and master's and doctoral candidates trained.